Why Do Users Contribute to Firm-Hosted User Communities? The Case of Computer-Controlled Music Instruments - Jeppesen, Lars Bo; Frederiksen, Lars (Organization Science, 2006)
Studies of the sources of innovations have recognized that many innovations are developed by users. However, the fact that firms employ communities of users to strengthen their innovation process has not yet received much attention. In online firm-hosted user communities, users freely reveal innovations to a firm's product platform, which can put the firm in a favorable position (a) because these new product features become available to all users through sharing on a user-to-user basis, or (b) because it allows the firm to pick up the innovations and integrate them in future products and then benefit by selling them to all users. We study the key personal attributes of the individuals responsible for innovations, namely the innovative users, to explain creation of value in this organizational context. The main question is why such users contribute to firm-hosted user communities. Analyzing data derived from multiple sources (interviews, a Web-log, and questionnaires), we find that innovative users are likely to be (i) hobbyists, an attribute that can be assumed to (positively) affect innovators' willingness to share innovations, and (ii) responsive to “firm recognition” as a motivating factor for undertaking innovation, which explains their decision to join the firm's domain. In agreement with earlier studies, we also find that innovative users are likely to be “lead users,” an attribute that we assume to affect the quality of user innovation. Whether or not a firm-hosted user community can be turned into an asset for the firm is to a great extent conditional on the issues studied in this paper.